Blood on the Trail : a Jeremiah Halstead western - McCauley, Terrence (McCauley, Terrence. Jeremiah Halstead western., 2022)
"Award-winning, critically acclaimed author Terrence McCauley has drawn comparisons to Elmore Leonard for his skilled writing of traditional historical Westerns with a crime fiction soul. Now be brings his signature historical accuracy, three-dimensional characters, and non-stop, adrenaline-fueled action to the first in a brand new series featuring Jeremiah Halstead. He may be the newest Deputy Marshal in the Montana Territory, but it doesn't take long for him to find himself in a mess of trouble... Silver Cloud, Montana. A mining town welcome to all seeking to make their fortune. And a place where a lawman has to watch his back before some hard case empties his pistol into it. Deputy U.S. Marshal Jeremiah Halstead is escorting notorious outlaw John Hudson across the territory for trial when he's ambushed by Hudson's gang. Although outnumbered and outgunned, Halstead puts the blast on a couple of the bushwhackers without giving up. Hudson holes up in Silver Cloud until the dust settles. The folks in Silver Cloud, though, are none too happy playing host to the lawman or his kill-crazy prisoner. Unable to trust the sheriff to back his play, Halstead finds himself standing alone against Hudson's gang as they slip into town, recruiting gunmen to help free their leader. Except for Ed Zimmerman. He's spent his whole criminal life in John Hudson's shadow. He wants Hudson dead and buried so he can become the leader of the gang. And if he has to, he'll put everyone in Silver Cloud six feet under--including Deputy U.S. Marshal Halstead..." --